Normalizing extreme imprisonment : the case of life without parole in California - Vannier, Marion, 1981- (Oxford : Oxford University Press, 2021)
A critical examination of life imprisonment without the possibility of parole (LWOP). This book presents a case study of the 'normalization' of LWOP and the extent to which groups and individuals within civil society who challenge capital punishment have helped normalize LWOP by fostering the belief that it is humane and merciful.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on June 7, 2021).
Keywords: Life imprisonment -- California; Corrections -- California; True Crime; Social services & welfare, criminology